Experimental Investigation of Non-Isolated Dust Particles on the Plasma Characteristics in Direct Current System - Abbas, Qusay Adnan; Edan, Rabah A (Al-Nahrain Journal of Science, 2018)
This paper reviews the radial profile of plasma parameters in the present and absent of non-isolated dust particles at different positions from the cathode surface. The results of voltage and current discharge shown that the present of dust did not effect of the behavior of discharge voltage but it decreased the discharge current. However, the measurement of radial distribution of plasma parameters along the cathode at different distance (2 cm and 4 cm) from it shown that, all plasma parameters are non-homogenous distribution along the cathode in the cathode sheath and plasma bulk. Moreover, according to radial profile of plasma potential, the charge of copper dust particles is negative in the plasma sheath but it is charged postively in the plasma bulk.